Underfive KMS utilizationin Marunda North Jakarta - Titi Sunarwati Sularyo (Paediatrica Indonesiana, 1999)
A prospective study was carried out on 102 underfives by home visits in Marunda, North Jakarta to obtain data on identification, and the underfive mortality in the family. The KMSs were reviewed in terms of, among others, its utilization and the immunization state. It revealed that the KMSs were over distributed (in 70.6% of children), but underutilized (83.3%), in a sense that only in 16.7% were the growth curves (weight curve) graphically plotted on the growth charts, and only in 21.6% were the KMS kept by the child/family. A proper utilization of the KMS was considered crucial as it was significantly related to improvement of the underfive immunization coverage (p<O.05) and very significantly related (p<0.01) to reduction in underfive mortality.